Medical Students’ Satisfaction with References Services in Afe Babalola University, Ado Ekiti - Saliu, Abdulfatai; Usman, Khadijat Asabe; Yaya, Japheth Abdulazeez (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2024)
The study was conducted on the medical students’ satisfaction with references services in Afe Babalola University, Ado Ekiti, Nigeria, while the data collected for the study were analyzed using frequency tables and percentage. Observation was used to determine the types of reference services and it was found that five (5) out of seven (7) reference services are provided in the library. these include CAS, user educator, Reprographic services, select dissemination of information, computerized reference sources and it was discovered that purpose of using reference section is that it enhancing the use of the resources and services of the library, it save precious time of the readers, supporting research and learning, leisure and recreation and it helps readers in locating the sources of information relevant to their needs, the study further discovered that referral services, Selective Dissemination of Information (SDI) Current awareness services, and Photocopying services that are used on a daily basis while it also discovered that inability of reference librarians to utilize new technologies to provide reference services, lack of policy implementation, lack of policy implementation, inadequate qualified staff and poor internet connectivity were the major problems affecting the provision of reference services. In conclusion the study made some recommendations which include that: management of the libraries should look toward the implementation of other medium of reference service delivery which has not been implemented in their libraries and there should be constant training and retraining of library personnel in the reference section to upskill and learn the new method of reference service delivery; and Library policies must be updated regularly.